جماليات المدائح النبوية عند شعراء العصر الحديث - - حنكة, قويدري, هنية سهيلة (Univesity of El-Oued, 2022)
حاولنا من خلال بحث مذكرتنا الموسوم بجماليات المدائح النبوية عند شعراء العصر الحديث الإحاطة بأهم جوانب الموضوع بداية من تناول غرض المديح كأهم الأغراض الشعرية في الأدب العربي لما يمثله من امتداد تاريخي، وإنتاج أدبي، عبر مراحل تاريخية، ومحطات أدبية. بداية من تعريفه وشرح مفهومه، وكشف ماهيته بصفة عامة، ثم تعريف المديح النبوي بصفة خاصة بشكل أكثر تفصيل. ثم انتقلنا إلى عرض الزوايا التي تناول من خلالها الشعراء مدح الرسول صلى الله عليه وسلم، فمنهم من تغنى بمدح صفاته الخَلقية والخُلقية، ومنهم من هزه الشوق إلى زيارة قبره صلى الله عليه وسلم، أو مدينته أو مسجده، فتدفقت قرائحهم سيلا جارفا تذكر سيد البرية، وتشيد بشمائله الربانية. ثم كان لا بد لنا من استقراء مضامين قصائد المديح، ودراسة شكلها من ناحية الوزن والقافية والبحور المناسبة لهذا الغرض، كخصائص تميز هذا النوع من الشعر في الأدب العربي. ومن أهم الجوانب كذلك التي تناولنا من خلالها دراسة قصيدة المديح النبوي الصورة الشعرية من كناية ومجاز واستعارة وتشبيه، وكيف أبدع شعراء المديح النبوي في تصوير حياته صلى الله عليه وسلم وكل ما يتعلق بها من قول أو عمل أو تقرير. وكان للزخرفة اللفظية الحظ الأوفر في شعر المديح، باعتبارها جانبا مهما في تزيين الأسلوب، وجمال التركيب، إن على مستوى اللفظ أو على مستوى الجملة. وقد اعتمدنا على مراجع ومصادر قديمة وحديثة، أهمها: ديوانا " كشف الغمة في مدح سيد الأمة " للبارودي و " الشوقيات " لأحمد شوقي ، ومن المراجع : "كتاب المدائح النبوية " لمحمود علي مكي . وكان الهدف الأساسي وراء بحثنا هذا هو إبراز الجانب الأدبي والفني بالدرجة الأولى في قصيدة شعر المديح النبوي في العصر الحديث معتمدين على مدونة شعرية لأهم شعراء المديح في العصر الحديث من أمثال أحمد شوقي ومحمود سامي البارودي. وفي الأخير نرجو من الله حسن الثواب أننا تمسحنا بسيرته صلى الله عليه وسلم، بغرض الإقتداء به، و اقتفاء We tried, through the research of our memorandum, which is marked with the aesthetics of prophetic praises for modern poets, to capture the most important aspects of the subject, starting with addressing the purpose of praise as the most important poetic purposes in Arabic literature because of its historical extension, literary production, through historical stages, and literary stations. Starting from defining it and explaining its concept, revealing its essence in general, and then defining the Prophet’s praise in particular in a more detailed manner. Then we moved to the presentation of the angles through which the poets addressed the praise of the Messenger, may God bless him and grant him peace. It praises its divine attributes. Then we had to extrapolate the contents of praise poems, and study their form in terms of weight, rhyme, and seas appropriate for this purpose, as characteristics that distinguish this type of poetry in Arabic literature. Among the most important aspects, through which we studied the poem of praise of the Prophet, is the poetic image of metaphor, metaphor, metaphor, and simile, and how the poets of praise of the Prophet innovated in depicting his life, may God’s prayers and peace be upon him, and everything related to it in terms of saying, work or report. The verbal decoration had the best luck in the poetry of praise, as it is an important aspect in decorating the style, and the beauty of the composition, whether at the level of the pronunciation or at the level of the sentence. We have relied on old and modern references and sources, the most important of which are: our collections of “Kashf Al-Ghamma fi Praising the Master of the Nation” by Al-Baroudi and “Al-Shawqiyat” by Ahmad Shawqi, and among the references: “The Book of Praises to the Prophet” by Mahmoud Ali Makki. The main objective behind our research was to highlight the literary and artistic aspect in the first place in the poem of praise of the Prophet in the modern era, relying on a poetic code for the most important poets of praise in the modern era, such as Ahmed Shawqi and Mahmoud Sami Al-Baroudi. And in the end, we ask God for a good reward that we have anointed us with his life, may God’s prayers and peace be upon him, for the purpose of imitating him, and tracing his trail
Keywords: مديح نبوي ,شعر حديث; Prophetic praise, modern poetry